Fetal Programming, Maternal Nutrition, and Oxidative Stress Hypothesis - Perrone, Serafina; Tataranno, Maria Luisa; Santacroce, Antonino; Bracciali, Carlotta; Riccitelli, Marina; Alagna, Maria Gabriella; Longini, Mariangela; Belvisi, Elisa; Bazzini, Francesco; Buonocore, Giuseppe; on behalf of the “Gruppo di Studio di Biochimica Clinica Neonatale della Società Italiana di Neonatologia” (Journal of Pediatric Biochemistry, 2016)
Fetal programming occurs when the normal pattern of fetal development is disrupted by an abnormal stimulus or an “insult” during intrauterine life, which leads to adaptations by the fetus to allow its survival but could finally result in permanent structural and physiological changes with long-term consequences in adulthood. The availability of nutrients, hormones, and respiratory gases is the principal determinant of fetal growth and offspring's subsequent health. Fetal nutrient and oxygen availability depend on the rate of transfer across the “placental barrier.” Nutritional status of the mother is also important: both maternal undernutrition and/or overnutrition during early gestation may increase the incidence of cardiovascular and metabolic disorders in the offspring in later life. Oxidative stress has been supposed to be the link between adverse intrauterine environment and later elevated risks of chronic diseases. It is an important initiating mechanism underlying the programming process due to suboptimal nutrition. Antioxidant vitamins, proteins, and trace elements can be compromised under condition of poor maternal nutrition leading to oxidant/antioxidant imbalance during pregnancy. On the other hand, maternal overnutrition is associated to chronic inflammatory states that increase free radicals' production. Developing dietary strategies to optimize maternal nutrition is necessary to supply the fetus with appropriate substrates and to avoid fetal redox status disruption.
Keywords: oxidative stress; nutrition; programming; fetus; newborn; placenta